PENGUKURAN TINGKAT KEPUASAN WISATAWAN TERHADAP FASILITAS UMUM, PRASARANA UMUM, DAN FASILITAS PARIWISATA DI MALIOBORO PASKA REVITALISASI KAWASAN - Susetyarini, Oktari; Masjhoer, Jussac Maulana (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
One of the most favorite tourist attraction in Yogyakarta is Malioboro. Revitalization of Malioboro has been realized by arranging three main areas, which are Alun-Alun Utara, Malioboro, and Abu Bakar Ali Parking Park. The hard work of the Government of Yogyakarta and its related parties in the early stages of this arrangement and revitalization has shown its results. Now the three areas of revitalization has been well ordered and expected to have a positive effect to increase the number of visitors in Yogyakarta. Improving the quality of public facilities, public infrastructure, and tourism facilities should be in line with the increasing satisfaction of tourists visiting the region, because the satisfaction of tourists is one of the benchmarks of the success of a tourist attraction. For that, research need to be done to measure the level of customer satisfaction on the revitalization of Malioboro area. This study aims to (1) find out the quality of public facilities, public infrastructure, and tourism facilities; (2) to know the level of satisfaction of tourists visiting in Malioboro area after revitalization. This research is descriptive research by conducting survey. Sampling method is using Accidental Sampling Method with the number of samples of 100 respondents who visited Malioboro area. Data collection techniques use questionnaires, interviews, and observations. Then the method of data analysis using Importance Performance Analysis method. The researchers hope this research can give input for local government especially Technical Implemetation Unit of Malioboro Area Management in Yogyakarta Tourism and Culture Departement, in order to improve the quality of tourist attraction in Malioboro area.